TESTOSTERONE REPLACEMENT THERAPY IN MEN WITH HYPOGONADISM – REVIEW OF LITERATURE - Jakub Majewski,; Oliwia Wróblewska,; Maria Kaniecka,; Anna Karcz,; Barbara Pająk,; Małgorzata Dworniczak,; Sofiya Salash,; Aleksandra Romaniuk,; Hubert Bołdys-Żegocki,; Artur Koza, (International Journal of Innovative Technologies in Social Science, 2025)
Testosterone replacement therapy (TRT) is the fundamental intervention in the treatment of male hypogonadism. Despite many years of clinical experience, in recent years the benefits and risks of TRT have been intensely discussed. The aim of this review article is to summarize the current state of knowledge on the pathophysiology of hypogonadism, diagnostic criteria, indications and effects of therapy, taking into account different patient groups. An analysis of available scientific publications was conducted, including clinical trials, meta-analyses, and official expert guidelines. The results of the review indicate that testosterone therapy significantly improves sexual function in men (including libido and erection) and has a beneficial effect on well-being. An increase in muscle mass, improvement in body composition (increase in lean mass and reduction of visceral fat), and also an increase in bone mineral density were observed. At the same time, attention is drawn to possible adverse effects of TRT, such as the development of polycythemia (elevated hematocrit), inhibition of sperm production, and potential exacerbation of obstructive sleep apnea symptoms in some patients. Testosterone therapy can bring significant benefits in the treatment of hypogonadism, especially in terms of improving sexual function and overall quality of life. However, the choice of treatment should be tailored to the patient in each case, taking into account possible risks, such as cardiovascular risk or impact on fertility. Due to remaining uncertainties, further prospective studies are necessary to more precisely assess the long-term safety of testosterone therapy.